Current androgen receptor antagonists under investigation for resistant prostate cancer. Issue 2 (1st February 2022) - Nigro, Maria Concetta; Mollica, Veronica; Marchetti, Andrea; Cheng, Michael; Rosellini, Matteo; Montironi, Rodolfo; Cheng, Liang; Massari, Francesco
ABSTRACT: Introduction: The gold standard of medical therapy for advanced prostate cancer is based on the use of androgen-receptor inhibitors and taxane-based chemotherapy. Several new agents, such as enzalutamide, apalutamide, darolutamide and abiraterone, are now approved and currently used in clinical practice. Areas covered: We present a review of the literature on the current state of the art on the use of androgen receptors inhibitors for the treatment of castration-resistant prostate cancer. We also provide an update on recent significant progress and ongoing clinical trials, and discuss the underlying cancer biology of castration resistance. Expert opinion: The advent of second-generation androgen receptor inhibitors has radically changed the therapeutic landscape of advanced prostate cancer. Novel strategies targeting the androgenic signaling pathway are being evaluated in order to overcome resistance mechanisms, to optimize the sequence of drugs currently available and to develop new combinational approaches to improve survival outcomes of advanced prostate cancer patients. New clinical trials, predictive biomarkers research, and real-world experience may further improve clinical outcomes and guide clinicians in the decision-making process.